Peningkatan Pemahaman Guru-Guru MTS Jeneponto dalam Desain Penilaian Pembelajaran - Asham Bin Jamaluddin; Halifah Pagarra; Rachmawaty Rachmawaty; Abd Muis; Muhammad Ansarullah S. Tabbu; Hartono Hartono (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2023)
Assessment in learning is an important component in monitoring learning progress, learning outcomes, and detecting the need for continuous improvement of student learning outcomes. The purpose of this research is to provide strengthening and understanding of MTS Madaniyah Gunung Silanu, Jeneponto teachers in learning design and assessment. The methods used in this research are; a) Observation; b) Training; c) Independent / Structured Tasks; d) Task Review; and e) Evaluation. Based on the results of the implementation of this training activity, it can be concluded that there is an increase in the ability of MTS teachers regarding learning design and assessment. The results can be seen from the activities that run well and conducive and the positive response of the trainees to the questionnaire given with an average score of 3.47.